Essentials for a health service (London : Communist Party, 1946)
1946 1946 1940s 12 pages medical services which could later be readily incorporated in the National Health Service. This can be done by: (a) the rapid and courageous development of health centres. A start could be made in temporary or adapted buildings in areas where medical practice is largely contract or panel, as in this way there would both be the least opposition and the most urgent need for impovement. We would suggest, therefore, that you should consider the setting up of a special committee to consider how best this plan could be started, either under temporary central control or under such local authorities as would be ready to co-operate. Medical men for this service would require general post-graduate training, specially designed to fit them for working as members of a team of practitioners in a centre; (b) the carrying out of the medical provisions of the Education Act, that medical inspection and treatment of all types (except domiciliary care) be available for all children in the schools. This will require establishment of more school clinics and the special training of the doctors in preventive medicine, in child health, and in the treatment of sick children; (c) the opening up of beds in all mental hospitals where they have been closed or used for other purposes during the war. The number of medical appointments in the mental hospitals, many of which are greatly understaffed, should be increased and more psychiatric out-patient clinics should be provided. Post-graduate psychiatric training will be required by the doctors; (d) the reopening of sanatoria and the extension and modernisation of the tuberculosis services; (e) the immediate establishment of an industrial medical service. All factories employing over 3,000 employees, or smaller factories with greater industrial hazards, should have a whole time industrial medical officer; smaller factories should employ a part-time officer or share the services of a full-time officer. These requirements should be made com- 5 15X/2/103/357